The Effect of Titanium Nanostructure on Corrosion Resistance as Dental Implants: A Review - Fadhli Muhammad; Shintia Novia Sari; Bonita Dilasari (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2024)
Titanium is widely recognized as the most biocompatible metal due to the inert passive oxide layer that forms spontaneously on its surface. However, dental implants made of titanium and its alloys remain susceptible to corrosion when exposed to saliva for extended periods in the oral environment. Additionally, the presence of alloying elements in the alloy may raise concerns about potential toxicity concerns upon release into the human body. Consequently, there is an increasing need for research aimed at improving the mechanical properties and biocompatibility of dental implants made from both commercially pure titanium (CP Ti) and Ti alloys. This article provides a review of recent publications that investigate the impact of grain size reduction on ultrafine-grained and nanocrystalline CP Ti and Ti alloys. The article explores the modification of the oxide layer to nanotube TiO2 and its influence on corrosion resistance. The analysis of accumulated data provides a comprehensive understanding of the mechanisms underlying corrosion resistance improvement, offering valuable insights into the crucial directions for future research in this field.